Genetic differentiation of Trachurus japonicus from the Northwestern Pacific based on the mitochondrial DNA control region. (December 2013) - Song, Na; Jia, Ning; Yanagimoto, Takashi; Lin, Longshan; Gao, Tianxiang
<x xml:space="preserve">Abstract</x> Trachurus japonicus is a pelagic fish widely distributed from China, Korea to Japan. To examine the gene flow of T. japonicus between Chinese and Japanese coastal waters, eight populations were collected for the present study. Eighty-seven variable sites defined 168 haplotypes. The populations of T. japonicus showed high haplotype diversity (h) with a range from 0.964 ± 0.027 to 1.000 ± 0.016 and low nucleotide diversity with a range from 0.011 ± 0.006 to 0.015 ± 0.008. The topology of the neighbour-joining tree showed no significant genealogical branches or clusters corresponding to sampling localities. The starburst structure of the minimum spanning tree suggested a very recent origin for most haplotypes. Both pairwise Fst and analysis of molecular variance revealed no significant genetic differentiation throughout the range examined. The results of neutrality tests and mismatch distributions indicated that T. japonicus may experience a recent population demographic expansion.